Breakdown of Ohm’s law in molecular junctions with electrodes of single-layer graphene - Bâldea, Ioan; Chen, Yuhong; Zhang, Miao; Xin, Na; Feng, Yunxia; Feng, Jiajun; Jia, Chuancheng; Guo, Xuefeng; Xie, Zuoti (The journal of physical chemistry letters, 2024)
For sufficiently low biases, Ohm’s law, the cornerstone of electricity, stating that current I and voltage V are proportional, is satisfied at low biases for all known systems ranging from macroscopic conductors to nanojunctions. In this study, we predict theoretically and demonstrate experimentally that in single-molecule junctions fabricated with single-layer graphene as electrodes the current at low V scales as the cube of V, thereby invalidating Ohm’s law. The absence of the ohmic regime is a direct consequence of the unique band structure of the single-layer graphene, whose vanishing density of states at the Dirac points precludes electron transfer from and to the electrodes at low biases.